Nanomanufacturing - Rembiesa, David; Nevshehir, Noel; Society of Manufacturing Engineers ([Michigan] : Society of Manufacturing Engineers, 2006)
Nanomanufacturing highlights the current, near-term, and future applications of this technology. You will see how nanotechnology is transforming the way we manufacture products an authoritative top-down fabrication and bottom-up assembly techniques that use matter to build complex products with atom-precision
Title from title screen
Executive producer, Steven R. Bollinger
Keywords: Nanotechnology; Nanostructured materials